Back to standardised assessment: A dangerous policy for teachers’ work - Jade Wrathall; Marta Estellés (New Zealand Journal of Teachers' Work, 2025)
The current government is actively working towards reintroducing standardised assessment for children between Year 3 and Year 10 in reading, writing and mathematics. In this commentary, we unpack this policy introduced by stealth, its drivers and virtual consequences for teachers’ work based on research from both New Zealand and overseas. We argue that, despite the rhetoric, this policy seeks to foster choice and competition, control teachers’ work, and rationalise scarce resources. The policy will likely have several collateral effects on teachers’ work, including further narrowing of the curriculum, de-skilling of the profession and privatisation of education. We conclude the piece with a call for teachers, educational scholars and the public to fight back against this dangerous policy.